Artificial Collusion: Examining Supracompetitive Pricing by Q-learning Algorithms - Arnoud V. den Boer; Janusz M. Meylahn; Maarten Pieter Schinkel (Tinbergen Institute, 2022)
We examine recent claims that a particular Q-learning algorithm used by competitors 'autonomously' and systematically learns to collude, resulting in supracompetitive prices and extra profits for the firms sustained by collusive equilibria. A detailed analysis of the inner workings of this algorithm reveals that there is no immediate reason for alarm. We set out what is needed to demonstrate the existence of a colluding price algorithm that does form a threat to competition.
Keywords: C63; L13; L44; K21; 330; collusion; Q-learning; algorithm; pricing